Textbook of biology (grade 9th model textbook) - Malik, jawad mohsin (National book foundation Lahore, 2011)
Biology Textbook for 9th Class provides a comprehensive introduction to key biological concepts, covering topics such as cells, ecosystems, and human anatomy, with clear explanations and engaging illustrations for young learners.